Facilitating children’s communication in problem-solving activities with a coding toy: teachers’ semiotic mediation in early childhood education and care - Granone, Francesca; Pollarolo, Enrico (Frontiers in Psychology, 2025)
This study investigates the role of teacher mediation in facilitating children’s communication during problem-solving, play-based coding activities with Kubo, a screen-free coding toy, in Early Childhood Education and Care (ECEC) settings. Following an initial observation involving nine kindergarten teachers and 36 children, a workshop was held to identify elements that teachers considered relevant for facilitating children’s use of verbal and non-verbal communication. Key mediation elements, such as multimodal communication, planning, time, humor, and reflective questioning, were identified during the workshop and applied in a subsequent observation with the same participants. The findings reveal that these mediation strategies facilitated children’s communication and participation in the activity using a multimodal approach to support their problem-solving process. Teacher mediation facilitated children’s ability to articulate their thought processes, fostering a communicative and reflective learning environment. This study underscores the importance of various elements in teachers’ semiotic mediation and identifies specific strategies that show promise for engaging all children.